PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII SMPIT FUTURE ISLAMIC SCHOOL PEKANBARU - Anjastin, Melati Agmiika; Sakur, Sakur; Anggraini, Rini Dian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Data daily test results of students of class VII SMPIT Future Islamic School Pekanbaru provide information that the percentage of learners who reach the criteria masses of minimum is still low. This Study aims to improve the learning process and the student’s outcomes of mathematic learning by applying problem based learning model. This classroom action research with two cycles was conducted in class VII SMPIT Future Islamic School Pekanbaru in the second semester of academic year 2017/2018 to 20 students. The required data are qualitative and quantitative data. The research instruments used are mathematical learning instruments (syllabus, lesson plans, and student worksheets) and instruments for collecting data (cbservation sheets and outcomes of mathematic learning tests). Qualitative data were collected by observation technique and analyzed by descriptive narrative analysis. Quantitative data were collected by test technique and analyzed by descriptive statistics analysis. Based on the analysis of the observation sheets showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle I. The percentage of learners who achieved the minimum mastery criteria is increase. Frequency of learners who achieve the minimum completeness criteria increasingly. The average mathematics learning outcomes of the students showed an increase. This study concludes is implementation of problem based learning improved the learning process and the student’s outcomes of mathematic learning at class VII SMPIT Future Islamic School Pekanbaru in the second semester of academic year 2017/2018.Key Words: problem based learning, outcomes of mathematic learning, learning process